2017
DOI: 10.1108/intr-05-2016-0116
|View full text |Cite
|
Sign up to set email alerts
|

Sales agents vs the internet

Abstract: Purpose -The purpose of this paper is to analyze perceptions of service cannibalization from sales agents when faced with increased online sales, and their consequences on the employee. The authors assess the effect of service cannibalization perceptions on insecurity, satisfaction, alienation, sales agents' effort. The study also examines relationships between effects on sales agents' service sabotage during service delivery. Design/methodology/approach -Data were collected from 497 travel agency sales agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 96 publications
1
3
0
2
Order By: Relevance
“…This result aligns with previous research showing that work alienation can affect individual's intended behaviour (Tummers et al, 2014). Additionally, the relationship between work alienation and service sabotage was confirmed by Díaz et al (2017). Thus, it is important to pay attention to nurses who are facing work alienation to prevent further consequences.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result aligns with previous research showing that work alienation can affect individual's intended behaviour (Tummers et al, 2014). Additionally, the relationship between work alienation and service sabotage was confirmed by Díaz et al (2017). Thus, it is important to pay attention to nurses who are facing work alienation to prevent further consequences.…”
Section: Discussionsupporting
confidence: 89%
“…According to the COR theory (Hobfoll, 1989), abusive supervision can deplete subordinates' resources, prompting them to engage in withdrawal coping strategies such as alienation (Osei et al, 2022). Psychological distancing and alienation may lead subordinates to replace and restore their lost emotions, potentially triggering service sabotage (Díaz et al, 2017). Moreover, recent studies have shown that nurses who drift away from work exhibit poor work performance (Amarat et al, 2019) and display negative behaviours such as low morale, decreased competency, and reduced understanding of policies (Özer et al, 2019).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…1) Toma de decisión (Familiar/personal de salud/paciente) Con respecto a este tema, el artículo realizado por Rubio et al (25) mostró que la mayoría de quienes optan por un manejo conservador lo hacen por padecer un estadio de la enfermedad que no tenía posibilidades de mejora con algún tratamiento de sustitución renal, presentaban deterioro funcional y/o cognitivo y también por decisión propia. (25) En concordancia con el artículo anteriormente mencionado el estudio realizado por Teruel J et.al (27) . Las mismas razones se repitieron en este estudio, sin embargo, este último también reveló que existía un grupo de pacientes que rechazan la terapia a pesar de que no presentaban ninguna contraindicación.…”
Section: Resultsunclassified
“…Se realizó una lectura crítica con el fin de evaluar la calidad metodológica de los artículos seleccionados.se utilizó una pauta con 12 indicadores "Guía práctica de lectura crítica de artículos científicos originales en Ciencias de la Salud" (25) . Se consideró que un artículo era de alta calidad si cumplía con más del 80% de los criterios, de calidad media si cumplía con 50-80% y de baja calidad si cumplía con menos del 50%.…”
Section: Lectura Críticaunclassified
“…Strain represent reactions resulting from being stressed for a long time. Work and social relationships are the most common sources of stress in the organisational environment (Díaz et al, 2017). Stress often depletes individuals' resources.…”
Section: Conservation Of Resources Theory (Cor)mentioning
confidence: 99%